Fate of sulphur during simultaneous gasification of lignin-slurry and removal of hydrogen sulphide over calcium aluminate supported nickel oxide catalyst. (10th January 2017) - Koido, Kenji; Watanabe, Yutaro; Ishiyama, Tomoyuki; Nunoura, Teppei; Dowaki, Kiyoshi
Abstract: The simultaneous process of synthesis gas production via lignin slurry gasification and high-temperature removal of hydrogen sulphide from the synthesis gas over calcium aluminate supported nickel oxide catalyst (NiO/CaAl2 O4 ) was investigated. The goal of this study was to clarify the effects of the operating temperature (750–950 °C), moisture content of the lignin slurry (73–90 wt%), and catalyst loading (0.00–0.61 g-catalyst/g-feedstock) on the sulphur balance of the process and to determine the appropriate catalyst loading with cleaner biosyngas via utilisation of the sensible heat for smaller additional heat, which is maintained at the temperature of the gasifier. The biosyngas generated from gasification of lignin slurry, which contained hydrogen sulphide (H2 S) and carbonyl sulphide (COS), was subjected to sulphur removal catalysed by NiO/CaAl2 O4 ; a sulphur yield on NiO/CaAl2 O4 of 0.14 mmol/g-lignin was achieved at the moisture content of 80.0 wt%, the reaction temperature of 900 °C, and the catalyst loading of 0.16 g-catalyst/g-feedstock. For the catalytic H2 S removal system applicable to solid oxide fuel cells, the performance efficiency was introduced to discuss the optimal catalyst loading amount; the performance efficiency was 0.63–0.72 S-mol%·g-lignin/kJ for the catalytic operations while 0.33 S-mol%·g-lignin/kJ for non-catalytic operation. Graphical abstract: Image 1 Highlights: Effects of operating gasifying conditions on the sulphur balances were clarified. Subsequent sulphur removal over NiO/CaAl2 O4 surface was also investigated. The catalyst decreased 17.6 S-mol% of sulphur compared with that of non-catalytic. The catalyst loading for high sulphur purity and low additional heat were proposed.